Saberes mobilizados por um grupo de professoras diante do desafio de integrar a Literatura infantojuvenil e a Matemática - Montezuma, Luci Fátima (2010)
Starting from the point that the continual formation of teachers must give opportunities to reflect about its own practice, to live classroom experiences from the situations developed in the courses and gain access to a theoretical foundation, we try to investigate which knowledge is mobilized, built and/or meant again by a group of elementary school teachers in an extension course before the challenge of integrating the juvenile literature and math. Related to the formation of teachers, knowledge and knowledge base to the teaching, strategies of formation and connection of literature with math, we chose among some topics of discussion Alarcão, Charlot, Fiorentini et al, Gauthier et al, Grando, Imbernón, Machado, Mizukami et al, Nacarato, Nóvoa, Oliveira, Passos, Ponte, Schön, Serrazina, Shulman, Smole, Tardif and Zeichner. In a qualitative approach we aimed to identify and analyze in this context the knowledge that was mobilized related to the general pedagogical knowledge as well as the specific ones related the professional development of the teachers before several formative strategies that were adapted during the course as reflection, team work, narratives, pedagogical interferences and reflexive observation by the teachers of the video classes, and also identify and analyze the potentialities of using the methodology of the connection of juvenile literature with math to the teaching. The analysis of data signals that the knowledge mobilized by the teachers was multiple and from different sources; it indicates that changes in general knowledge as well as in specific one in math, new meanings of some conceptions that the collaborative teachers related the teaching posture to the contents, values, attitudes and behavior. We also noticed that the value given to the time of group work by the teachers with the sharing of knowledge, legitimation of some teaching actions related to the contents, ways of performance, pedagogical resources adapted and mainly related to some concepts of geometry, the treatment of information and fractional/rational numbers that were the topics studied during the course; the acknowledgement and acceptance of the differences in classroom. We raised evidences that the professional knowledge of the teachers was meant with practice since they started to face Math presented in books in a different way, conceiving a new way of mobilizing the students to a learning process, what means a bigger flexibility in the base of the knowledge to the teaching and offer potentialities for a professional development.